Optimal LQG controller to adjust the rudder supplying water to the turbine of small and medium hydro power plants - Le Ngoc, Giang; Dang Tien, Trung; Tran Xuan, Tinh; Thi Dieu, Linh Nguyen (Ingeniería Solidaria, 2021)
Introduction: This paper is the result of the research “Optimal LQG controller to open rudder supplying water to turbine of small and medium hydro power plants” developed in the Electric Power University in Vietnam in 2019.Problem: To maintain the frequency of the emitted voltage of the generator at the nominal value of 50 Hz, the authors present a solution to apply the optimal control theory to create a command to control the rudder angle to adjust the water flow into the turbine.Objective: The article presented about the order value formation algorithm, to stabilize the frequency of transmission voltage at 50 Hz standard value.Methodology: In this paper, the laws to control the rudder supplying water to turbine of small and medium hydro power plants are synthesized by optimal control theory. To establish optimal control rules, the paper proposes using the Kalman filter to estimate the state of the object. By that, the frequency of generated voltage will be stabilized under changing load. The efficacy of the steady and dynamic performance of the control strategy was verified using Matlab/Simulink software.Results: The proposed system can compensate for power fluctuations and is effective in terms of power regulation.Conclusion: The algorithm presented in the paper is the basis for setting up the software when when designing and manufacturing the turbine - generator combination. Applying this algorithm, the process of adjusting the transmitted power according to the required load will be performed with quality.Originality: This paper’s contribution lies in its employment of an effective optimal LQG control for varying operating conditions.Limitations: The authors need to spend more time to the development and and test this algorithm and and implementing it in practice.
Keywords: optimal control; rudder; hydropower turbine; stabilize the frequency